Administration of hioscine in decreasing the time of duration of childbirth labor active phase in primigravida women - Rocano-Rojas, León (2019)
The objective of this research was to determine the effectiveness of the administration of hyoscine in the reduction of the duration of childbirth labor, active phase in primigravida women users of the Hospital Materno Infantil Carlos Showing Ferrari. Amarilis. January-June 2017; the study was quasi experimental, prospective, longitudinal design, with 64 pregnant women: 32 for the control group and 32 for the experimental group, the instrument was observation sheet; the results were: 1. More frequent ages between 18 to 29 years, all of urban area, and marital status cohabiting 30 to 37%. 2. Mechanism of action of all pregnant women was at the isthmus level of the cervix in the control group. 3. Mean score of the Bishop modified index before the application of the stimulus, the experimental group was 6,22 and after the stimulus 11,44, increasing 5,22 points and in the control group before the stimulus 5,38 and after the stimulus 5 , 47 increasing only 0.09 points, 4. Time duration of childbirth labor in active phase was in the experimental group from 1 to 3 hours 30%, 4 to 6 hours 19%, more than 6 hours 1% while in the control group 1 to 3 hours 1%, 4 to 6 hours 22%, more than 6 hours 17%. Conclusion: we accept the hypothesis of research that the administration of hyoscine has a significant effect on the decreasing time of duration of childbirth labor in active phase in primigravida women.